Amyloid β concentrations and stable isotope labeling kinetics of human plasma specific to central nervous system amyloidosis. Issue 8 (19th July 2017) - Ovod, Vitaliy; Ramsey, Kara N.; Mawuenyega, Kwasi G.; Bollinger, Jim G.; Hicks, Terry; Schneider, Theresa; Sullivan, Melissa; Paumier, Katrina; Holtzman, David M.; Morris, John C.; Benzinger, Tammie; Fagan, Anne M.; et al.
Abstract: Introduction: Cerebrospinal fluid analysis and other measurements of amyloidosis, such as amyloid‐binding positron emission tomography studies, are limited by cost and availability. There is a need for a more practical amyloid β (Aβ) biomarker for central nervous system amyloid deposition. Methods: We adapted our previously reported stable isotope labeling kinetics protocol to analyze the turnover kinetics and concentrations of Aβ38, Aβ40, and Aβ42 in human plasma. Results: Aβ isoforms have a half‐life of approximately 3 hours in plasma. Aβ38 demonstrated faster turnover kinetics compared with Aβ40 and Aβ42. Faster fractional turnover of Aβ42 relative to Aβ40 and lower Aβ42 and Aβ42/Aβ40 concentrations in amyloid‐positive participants were observed. Discussion: Blood plasma Aβ42 shows similar amyloid‐associated alterations as we have previously reported in cerebrospinal fluid, suggesting a blood‐brain transportation mechanism of Aβ. The stability and sensitivity of plasma Aβ measurements suggest this may be a useful screening test for central nervous system amyloidosis.